Paediatric dengue life-threatening symptoms recognition amongst carers in community / Nur Atifah Mohd Naim - Mohd Naim, Nur Atifah (2012)
Malaysia carries a high burden of dengue and dengue hemorrhagic fever (DHF). This disease carries significant morbidity and mortality risks especially amongst the paediatric population. Dengue is one of the world's significant arthropod-borne diseases with high prevalence in tropical and subtropical regions. The number of dengue cases have increased by about 30-fold in the last 40 years. Worldwide, there are about 50 million cases of dengue infection annually (Brooks, Carroll, Butel & Morse, 2004) with an estimated 500,000 cases of dengue hemorrhagic fever and 22,000 deaths occurring mainly amongst the pediatric population (http://www.who.int/csr/disease/dengue/impact/en/). Today, over 2.5 billion people, almost one third of the global population, live in high risk areas for this potentially deadly virus (Mazrura et al, 2010). In addition, an estimated 100 countries worldwide have dengue fever classified as endemic disease (Syed et al, 2010). The number of countries being affected has continued to rise as compared to in 1970 when only nine countries experienced epidemic DHF (http://www.who.int/csr/disease/dengue/en/).